Clinical outcome and cost-effectiveness of a 1-year nutritional intervention programme in COPD patients with low muscle mass: The randomized controlled NUTRAIN trial. Issue 2 (February 2020) - van Beers, Martijn; Rutten-van Mölken, Maureen P.M.H.; van de Bool, Coby; Boland, Melinde; Kremers, Stef P.J.; Franssen, Frits M.E.; van Helvoort, Ardy; Gosker, Harry R.; Wouters, Emiel F.; Schols, Annemie M.W.J.
Summary: Background and aims: The efficacy of nutritional intervention to enhance short- and long-term outcomes of pulmonary rehabilitation in COPD is still unclear, hence this paper aims to investigate the clinical outcome and cost-effectiveness of a 12-month nutritional intervention strategy in muscle-wasted COPD patients. Methods: Prior to a 4-month pulmonary rehabilitation programme, 81 muscle-wasted COPD patients (51% males, aged 62.5 ± 0.9 years) with moderate airflow obstruction (FEV1 55.1 ± 2.2% predicted) and impaired exercise capacity (Wmax 63.5 ± 2.4% predicted) were randomized to 3 portions of nutritional supplementation per day (enriched with leucine, vitamin D and polyunsaturated fatty acids) [NUTRITION] or PLACEBO (phase 1). In the unblinded 8-month maintenance phase (phase 2), both groups received structured feedback on their physical activity level assessed by accelerometry. NUTRITION additionally received 1 portion of supplemental nutrition per day and motivational interviewing-based nutritional counselling. A 3-month follow-up (phase 3) was included. Results: After 12 months, physical capacity measured by quadriceps muscle strength and cycle endurance time were not different, but physical activity was higher in NUTRITION than in PLACEBO (Δ1030 steps/day, p  = 0.025). Plasma levels of the enriched nutrients ( p  < 0.001) were higher in NUTRITION than PLACEBO. Trends towards weight gain in NUTRITION and weight loss in PLACEBO led to a significant between-group difference after 12 months (Δ1.54 kg, p  = 0.041). The HADS anxiety and depression scores improved in NUTRITION only (Δ-1.92 points, p  = 0.037). Generic quality of life (EQ-5D) was decreased in PLACEBO but not in NUTRITION (between-group difference after 15 months 0.072 points, p  = 0.009). Overall motivation towards exercising and healthy eating was high and did not change significantly after 12 months; only amotivation towards healthy eating yielded a significant between-group difference (Δ1.022 points, p  = 0.015). The cost per quality-adjusted life-year after 15 months was EUR 16, 750. Conclusions: Nutritional intervention in muscle-wasted patients with moderate COPD does not enhance long-term outcome of exercise training on physical capacity but ameliorates plasma levels of the supplemented nutrients, total body weight, physical activity and generic health status, at an acceptable increase of costs for patients with high disease burden.